On the effect of random power availability in wireless power transfer systems with physical layer security - Tarrías Muñoz, Antonio; Romero-Jerez, Juan Manuel; López-Martínez, Francisco Javier (My University, 2020)
In this paper, we evaluate the performance of wireless powered communication systems from a physical layer security perspective. Our aim is to determine under which conditions the random power availability due to wireless power transmission using a dedicated power beacon impacts the maxi- mum secrecy rate, compared to its deterministic counterpart. We also investigate the effect of line-of-sight condition on the system performance. Analytical expressions are derived for some specific scenarios, which are combined with Monte Carlo simulations. We see that under a moderate line-of-sight condition in the wireless power transfer link, the secrecy performance is barely affected.
Keywords: Sistemas de comunicaciones inalámbricos; Sistemas de telecomunicaciones - Evaluación; Seguridad de la capa física; physical layer security; wireless powered communications